Kiralananın sözleşmenin sona ermesinden önce iadesi - Erzengin, Ertuğrul Doğan (My University, 2020)
Türk hukukunda kiralananın sözleşmenin sona ermesinden önce geri verilmesi; Türk Borçlar Kanunu m. 325 (OR Art. 264) hükmünde, kira sözleşmesinin genel hükümleri bölümünde düzenlenmiştir. Kira sözleşmesi, kullanma ve yararlanma hakkı veren sözleşmelerden uygulama alanı en geniş olan sözleşme tipidir. Kiralananın kira sözleşmenin sona ermesinden önce geri verilmesi hususu ülkemizde sıklıkla karşılaşılan bir durumdur. Bu bakımdan Türk Borçlar Kanunu m. 325 hükmü ülkemizde geniş bir uygulama alanını haizdir. Çalışmamızda mehaz İsviçre Borçlar Kanunu ve ülkemiz Yargı uygulaması temelinde Türk Borçlar Kanunu m. 325 hükmü ayrıntılı biçimde incelenmeye çalışılmıştır. Çalışmamızın ilk bölümünde TBK m. 325 hükmünün tarihsel gelişimi, hükmün genel özellikleri, niteliği ve uygulama alanı incelenmiştir. İkinci bölümde hükmün uygulanabilmesi için gereken şartlar; üçüncü ve son bölümde kiralananın sözleşmenin sona ermesinden önce geri verilmesinin hüküm ve sonuçları izah edilmiştir.

In Turkish Law, return of the leased object before the expiration of a contract is regulated in article 325 of Turkish Code of Obligations, which is part of the general provisions of the lease contract. Lease agreement is the contract with the widest application area among the agreements that grant the right to use and benefit. It is frequently encountered in our country that the leased object is given back to the lessor before the end of the lease agreement. In this respect, article 325 of Turkish Code of Obligations has a wide application area in our country. In this study, article 325 of the Turkish Code of Obligations is analysed on the basis of Swiss Code of Obligations and Judicial practice in Turkey. In the first part of the study, the historical development of the provision, the general characteristics of the provision, the nature and application area of ​​the provision were examined. In the second part of the study, conditions for the application of the provision were examined. In the third part of the study, the terms and results of the return of leased object before the execution of the contract are explained.
Keywords: 325; Civil law; Early Release; Erken iade; Erken Tahliye; Expiration of The Lease Agreement; Fesih; Hukuk; Kira bedeli; Kira sözleşmesi; Kira sözleşmesinin sona ermesi; Kiralanan; Law; Leased; Mahsup Lease Contract; Makul Süre İle Sorumluluk; Medeni hukuk; Rent; Responsibility with Reasonable Time; Set-off; TBK m. 325; Termination; TOR Art